"The Roman Giant": Overgrowth Syndrome in Skeletal Remains from the Imperial Age. (28th May 2013) - Minozzi, S.; Pantano, W.; Catalano, P.; di Gennaro, F.; Fornaciari, G.
Abstract A very tall skeleton was found during archaeological excavations in the territory of Fidenae, an administrative centre of the Roman territorial organization, situated along the Via Salaria about 7 km north of Rome (Italy). The individual was a young male, dated back to the Imperial Age (3rd century AD), presenting a very tall but normally proportioned stature, estimated around 202 cm. The long bones showed incomplete epiphyseal union; therefore, the stature would probably have been taller, if he had lived longer. In this work, the metric data are compared with those from the Roman Imperial Age population, and differential diagnosis is discussed. The skeletal evidence is characteristic of a form of gigantism, a rare growth disease that may be linked to different syndromes. The most common etiology is associated with a dysfunction of the pituitary gland, which causes overproduction of the growth hormone (hGH) during childhood. This endocrine disorder stimulates cartilaginous activity at the growth plate, delaying epiphyseal fusion and resulting in increased bone length. Copyright © 2013 John Wiley & Sons, Ltd.